Hoe economie het probleem werd En wat eraan te doen valt - Byttebier, Koen (Socioeconomics & law, 2022)
The legal systems that shape capitalist societies worldwide contribute to a number of fundamental social problems. An ever-growing public and private debt, environmental pollution, an increasing polarization between rich and poor, and a globally unjust fiscal and financial system are examples of this. from. The capitalist system itself does not address these problems. However, the main legal building blocks of the capitalist socio-economic system are remarkably simple, namely money and the way in which it is created, the (capital) company form and the (neo)liberal state organization that wants to make the markets as free as possible. In How Economics Became the Problem (and What to Do About It), the author, as a specialist in the field, provides a critical analysis of capitalist economics and provides insights into how, for the benefit of our societies, we be able to use the prevailing legal instruments completely differently. The book is the Dutch version of the original English version entitled How Economics Became the Problem. An urgent call to legal action. The Russian translation of the book will be published in 2021. A Chinese version of the book is currently in press.